The Impact of Digital Transformation on Auditing Practices in the Modern Economy - Dimitrov, Kiril (Research Papers, 2025)
Digital transformation is significantly changing audit practices, with the introduction of new technologies such as artificial intelligence (AI), machine learning, blockchain and big data transforming the traditional audit process. These technologies facilitate the automation of routine tasks, improve the accuracy and efficiency of audits, and provide deeper real-time data analysis.